Abandoned, But Not Forgotten Heritage: Former Industrial Enterprises in Cultural and Urban Russian Landscapes. (2nd September 2022) - Kochetkova, Elena; Petrova, Anna
ABSTRACT: This paper examines Russian industrial heritage and its interactions with society. It focuses on changing identities and the transformation of industrial enterprises from connecters to the future in Soviet times, to bridges to both the past and the future for different social groups in post-Soviet Russia. Based on regional examples from the Russian northwest, this article analyzes the trajectories of industrial enterprises from urban centers to peripheries, and the socio-cultural appropriation they experience. Based on newspaper articles, online comments of citizens, and materials from Internet communities, this analysis explores discussions about the reuse of abandoned industrial heritage in Russia. First, it shows how industrial enterprises have moved from centers of the future to peripheries of the past during the last century, and continue to do so at present. Second, it examines how citizens interact with them today, producing nostalgia for the "lost" Soviet past and using abandoned buildings for stalker adventures. The paper concludes that abandoned enterprises transform from industrial centers to cultural sites, binding past, present and future together in a temporal conjunction where three unique temporalities co-exist and overlap: the socialist past, the modern Russian present, and imagined futures. Abandoned heritage is a dynamic participant in cultural and social activities but simultaneously it signifies disappearing industrial socialism.